2013
DOI: 10.1128/iai.00214-13
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Leishmania infantum chagasi Metacyclic Promastigotes by Sterol Depletion

Abstract: The infectious metacyclic promastigotes of Leishmania protozoa establish infection in a mammalian host after they are deposited into the dermis by a sand fly vector. Several Leishmania virulence factors promote infection, including the glycosylphosphatidylinositol membrane-anchored major surface protease (MSP). Metacyclic Leishmania infantum chagasi promastigotes were treated with methyl-beta-cyclodextrin (M␤CD), a sterol-chelating reagent, causing a 3-fold reduction in total cellular sterols as well as enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…A Brazilian strain of Leishmania infantum (previously called L. chagasi ) (MHOM/BR/00/1669) was serially passaged in golden hamsters to maintain parasite virulence. Amastigotes were isolated from infected hamster spleens and allowed to transform to promastigotes in HOMEM (Hemoflagellate modified Minimal Essential Medium) with 10 % fetal calf serum (FCS) and hemin made from commercially available ingredients as previously described [ 8 ]. Serum-free medium (SFM) was prepared similar to HOMEM but lacking FCS and with additional biopterin, adenosine and bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Brazilian strain of Leishmania infantum (previously called L. chagasi ) (MHOM/BR/00/1669) was serially passaged in golden hamsters to maintain parasite virulence. Amastigotes were isolated from infected hamster spleens and allowed to transform to promastigotes in HOMEM (Hemoflagellate modified Minimal Essential Medium) with 10 % fetal calf serum (FCS) and hemin made from commercially available ingredients as previously described [ 8 ]. Serum-free medium (SFM) was prepared similar to HOMEM but lacking FCS and with additional biopterin, adenosine and bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Metacyclic promastigotes could not be recovered from similar cultures of avirulent promastigotes (data not shown). In some experiments, metacyclic promastigotes were incubated in 25 mM MβCD (Sigma, St. Louis, MO) freshly prepared in RPMI 1640 (GIBCO) at a cell density of 2 × 10 8 cells/ml at room temperature for 1 h to deplete cellular sterols, and then washed twice by centrifugation in Hanks’ balanced salt solution (GIBCO) as described [ 8 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPG avoids the ultimate step of the complement cascade through prevention of the attachment of the C5b-C9-complex to the parasite surface ( 83 , 84 ). On the other hand, GP63 inactivates C3b preventing the formation of the C5 convertase complex ( 85 , 86 ). Albeit, Dominguez et al showed that under physiological conditions 85–100% of L. donovani, L. infantum, L. major , and L. amazonensis promastigotes are killed by complement after 2.5 min in human blood ( 87 ).…”
Section: Overcoming the Immune Leishmanicidal Machinerymentioning
confidence: 99%
“…L . major parasites lacking these glycocalyx receptors are highly susceptible to complement killing (Joshi et al ., , Spath et al ., 2003b, Yao et al ., ). Genetic deletion of GP63 in L .…”
Section: The Complement Cascadementioning
confidence: 97%